PENGGUNAAN MEDIA AUDIO-VISUAL UNTUK MENINGKATKAN MINAT BELAJAR PAI DI SDN BANYU URIP II SURABAYA - Sabila Islami, Aisyah Beauty; Adilah Mazaya Nabilah; Munawir (STIT Sirojul Falah Bogor, 2024)
This research aims to increase the learning interest of class II students at SDN BANYU URIP II Surabaya through the use of audio visual media in learning Islamic Religious Education (PAI). The research uses the Classroom Action Research (PTK) method with two cycles, descriptive and naturalistic in nature. Research procedures consist of planning, action, observation, and reflection. The research results show that the use of audio-visual media can significantly increase students' interest in learning. In the first cycle, the average student learning outcome was 76.81%, increasing to 82.24% in the second cycle. This shows an increase in students' interest in learning through the use of audio-visual media in PAI learning. In conclusion, the use of audio visual media is effective in increasing students' interest in learning. With this media, students can learn more effectively, innovatively and have fun. The research results also show that learning with audio-visual media can improve students' memory and make learning more enjoyable. Therefore, it is recommended that teachers use audio-visual media wisely in the learning process to achieve optimal learning goals.